Spatial-frequency organization in primate striate cortex. - Silverman, M S (1989)
We measured the spatial-frequency tuning of cells at regular intervals along tangential probes through the monkey striate cortex and correlated the recording sites with the cortical cytochrome oxidase (CytOx) patterns to address three questions with regard to the cortical spatial-frequency organization. (i) Is there a periodic anatomical arrangement of cells tuned to different spatial-frequency ranges? We found there is, because the spatial-frequency tuning of cells along tangential probes changed systematically, varying from a low frequency to a middle range to high frequencies and back again repeatedly over distances of about 0.6-0.7 mm. (ii) Are there just two populations of cells, low-frequency and high-frequency units, at a given eccentricity (perhaps corresponding to the magno- and parvocellular geniculate pathways) or is there a continuum of spatial-frequency peaks? We found a continuum of peak tuning. Most cells are tuned to intermediate spatial frequencies and form a unimodal rather than a bimodal distribution of cell peaks. Furthermore, the cells with different peak frequencies were found to be continuously and smoothly distributed across a module. (iii) What is the relation between the physiological spatial-frequency organization and the regions of high CytOx concentration ("blobs")? We found a systematic correlation between the topographical variation in spatial-frequency tuning and the modular CytOx pattern, which also varied continuously in density. Low-frequency cells are at the center of the blobs, and cells tuned to increasingly higher spatial frequencies are at increasing radial distances.